the Impact of Monopoly or Industry Competition on Pricing of External Audit Services - Ali Ebrahimi Kordlar; Musa Javani Ghalandari; Kianoosh Ganji (مطالعات تجربی حسابداری مالی, 2016)
Existing theories predict two contradict relation between industry competition and audit fees. Industry competition reduces the agency problem between manager and stockholder of firms and also increases the accuracy of financial statement. It therefore decreases the assessment of risk by auditors and they are inclined to charge low audit fee for companies operating in competitive industry. On the other hand industry competition can increase the assessment of business risk by auditor, so it would be expected as the competition in industry rises the audit fee, the current study examine empirically "The impact of monopoly or industry competition on pricing of external audit services "with the information of 96 publicly-held companies listed in Tehran Stock Exchange (TSE) Between 2009-2016. The result of study shows the significant and negative relation between audit fee and industry competition. In other words, auditor charge low audit fee for client which operate in high competitive industry.